Review on the Effect of An Ayurvedic Management Protocol in Chronic Obstructive Pulmonary Disease (International Journal of Ayurveda and Pharma Research, 2024)
Considering the similarities noticed in the etiology and clinical features, COPD can be correlated to Tamaka shvasa among the Pranavaha srotodushti vikara, a condition where Pitta is involved along with Kapha and Vata. Rasayana is the main intervention in such a chronic disease and considering the Doshas and Rasayana, Virecana is the best preparatory Shodhana here to be administered for the patients. In Ayurveda, drug is denoted by the term ‘Bheshaja’ which is defined as the substance through which we can overcome the fear of disease. The ‘Upakarana’ which helps physician for maintaining the healthy condition or to alleviate disorders is said to be Bheshaja. Physician accomplishes the object ‘Vikara shamana’, by giving the appropriate Bheshaja according to different stages and conditions of the patient and disease. According to Ayurveda, action of a drug is based on its Guna, Virya, Vipaka and Prabhava. Fate of the drug always depends on Rasapancaka and it goes in line with modern pharmacodynamics. Besides that, the drug action also depends on the action of agni on that particular drug. In this article, a management protocol review on Chronic Obstructive Pulmonary Disease was carried out. The protocol selected and reviewed was Dipana with Panchakola curna in hot water, Snehapana with Kantakari ghrta, Abhyanga with Tila taila followed by Ushmasveda, Virecana with Vidangatanduladi curna and finally Pippali Vardhamana rasayana.